HVAC Commissioning Guidebook - Virta, Maija; Federation of European Heating and Airconditioning Associations (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2021)
Green buildings have become common in India and other countries in Asia. However, there is a concern regarding the performance of green buildings failing to meet the expectations of clients during the operation. One of the key reasons for this is poorly commissioned HVAC systems. In this publication we provide tools and knowhow for more efficient HVAC commissioning. It gives answers for four major questions: why commissioning is needed, how to perform proper commissioning, which key performance issues of common HVAC equipment need to be considered, and what kind of checklists are used during commissioning? It covers the entire commissioning process beginning with the owner's project requirements and commissioning design reviews. Then, it explains procedures during installation and start-up of equipment followed by the functional performance testing, seasonal commissioning and 10 months' operation review.This publication is developed by Indian Society of Heating, Refrigeration and Air Conditioning Engineers ISHRAE for Indian and Asian requirements in conjunction with the Federation of European HVAC Associations REHVA. The process steps described in this publication are in line with all major international building standards and green building certification schemes. Note: T&F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
1. Commissioning in Nutshell 2. Why Commissioning? 3. Initial Commissioning 4. Retro-Commissioning 5. Ongoing Commissioning 6. Commissioning Management 7. Typical Pre-commissioning and Startup procedures.
OCLC-licensed vendor bibliographic record.
Keywords: Heating; Ventilation; Air conditioning; TECHNOLOGY / Construction / Heating, Ventilation & Air Conditioning